Ações educativas sobre prevenção de acidentes infantis em curso de Design Gráfico - Keppler, Maria Aparecida Brandão Bonadio [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Education is indicated as an alternative for the reduction of child accidents, which are a serious worldwide public health problem that is still without a solution. There is a lack of informative material regarded to this theme, available for educational activities with the population, but Graphic Design courses can contribute in their elaboration, however this does not happen. This paper elaborates, applies and evaluates the effect of a teaching program in the knowledge related to the prevention of child accidents and the production of informative materials associated with the theme, with graduate students of Graphic Design course. Forty-nine graduate students of Graphic Design nocturne course took part, at a private Higher Education Institute at a city of the state of São Paulo, Brazil, with nearly 220 thousand inhabitants. It uses printed material, virtual texts and computers equipped with graphic softwares, Moodle environment and internet. As procedure: it elaborates a teaching program based on Behavior Analysis and in the Pilot Study results, with the objective that each participant be able to answer questions, to develop texts and to accomplish the graphic project of informative material related to the theme, as well as to use the project methodology and to produce the final report. It applies the teaching program through the Initial Questionnaire, seeking the identification of the participants’ profile, opinions, previous knowledge and the information they receive at the university about the theme; it accomplishes with the participants activities involving reading, questionnaires, research and elaboration of informative materials associated with the subject and evaluates using the Final Questionnaire to investigate the acquired knowledge and the participants’ opinion related to the accomplished activities; the Activities Registration Spreadsheet elaborated by the researcher to track the participants’ improvement...

A Educação é indicada como alternativa para a diminuição dos acidentes infantis, um sério problema de saúde pública mundial ainda sem solução. São escassos os materiais informativos relacionados à temática, disponíveis para atividades educativas com a população, mas cursos de Design Gráfico podem contribuir para elaborá-los, o que não ocorre. Esta pesquisa elabora, aplica e avalia o efeito de um programa de ensino nos conhecimentos a respeito da prevenção de acidentes infantis e na produção de materiais informativos referentes à temática, com graduandos de curso de Design Gráfico. Participam 49 graduandos de curso noturno de Design Gráfico, em Instituição de Ensino Superior numa cidade do Estado de São Paulo, Brasil, com aproximadamente 220 mil habitantes. Utiliza impressos, textos virtuais e computadores equipados com softwares gráficos, ambiente Moodle e Internet. Como procedimentos, elabora um Programa de Ensino embasado na Análise do Comportamento e nos resultados de Estudo Piloto, com o objetivo de que cada participante, esteja apto a responder questões, a desenvolver textos e a executar o projeto gráfico de material informativo a respeito da temática, bem como a utilizar a metodologia de projetos e a produzir relatório final. Aplica o Programa de Ensino por meio de Questionário Inicial, buscando identificar o perfil dos participantes, as opiniões, o conhecimento prévio e o recebimento de informações na universidade a respeito da temática; realiza com os participantes atividades envolvendo leituras, questionários, pesquisas e elaboração de materiais informativos referentes à temática e, avalia utilizando o Questionário Final para investigar o conhecimento adquirido e a opinião dos participantes relacionada às atividades realizadas; a Planilha de Registro de Atividades elaborada pela pesquisadora para acompanhar o aproveitamento dos participantes no processo do Programa e o Questionário...
Keywords: Artes gráficas; Ensino superior; Prevenção de acidentes; Material didatico; Graphic arts